Recuperación de la memoria intercultural para el fortalecimiento de la identidad comunitaria de los niños y niñas del Cecib Agustín Anguisaca de la comunidad el Calvario, cantón Saquisilí - Taco Chasi, Verónica Alexandra (2015)
The general objective of this research was to recover the intercultural memory for the strengthening the cultural identity in the children of the “Agustín Anguisaca” Intercultural Bilingual Educative Center, during the academic year 2014-2015. The investigated problem was: What is the influence about the recovery of the intercultural memory in the strengthening of the community identity?; the methods used in this study were: the deductive method for the study of fundamental categories and the investigated variables; the historical method for the collection of information related to the intercultural memory, the analytical –synthetic for the interpretation of results and the conclusions; and also techniques such as: the interview for collecting data about the cultural facts of the past; and the observation for registering the children’s behavior in relationship to culture. The achieved results were: the verification of the loss of intercultural memory by the influence of foreign customs and traditions, the loss of personal, familiar and community identity which provoke the cultural decadency. The contribution of this thesis is the elaboration of a guide of cultural practices in order to recovery the intercultural memory which describes ludic activities that will be socialized to strengthen community identity.